Optimal control and sensitivity analysis of COVID-19 transmission model with the presence of waning immunity in West Java, Indonesia. (2022) - Inayaturohmat, Fatuh; Anggriani, Nursanti; Supriatna, Asep Kuswandi
No abstract available